Photovoltaic versus Micro-Hydropower for Rural Non-Grid Connected Areas of Equatorial Sarawak - Prashobh, Karunakaran; Lau, Alvin KS; Reddy, Anr (UTEM, 2017)
There is currently a large expansion in photovoltaic installation worldwide especially in the temperate regions of the world which have tended to influence electrical power decisions in developing countries at the equator. This research clearly justifies hydropower over photovoltaic electricity generation in non-grid connected regions of equatorial Sarawak, Malaysia. A case study was made of photovoltaic installations versus micro-hydropower installation in these regions. There are problems of micro-hydroelectricity especially during dry seasons but this work justifies allocating more resources in improving micro-hydroelectricity research such that eventually it will produce enough electricity even with the low water flow rate of the dry seasons. This research can be done locally compared to photovoltaics whose research tends to be mostly imported into Malaysia. Some comparisons are made to grid connected hydroelectric dams to depict capabilities of this technology given sufficient research allocations.